Perbandingan Kualitas Pendidikan Antara Sekolah Negeri Dan Sekolah Swasta: Eksplorasi Pada Aspek Pembelajaran - Islami, Muhammad Fajri; Nasir; Rasid; Nurzaima; Mujiati, Mujiati (Kelola: Jurnal Manajemen Pendidikan, 2024)
This study investigates the quality of education in public and private schools, focusing on various aspects of learning. The research aims to understand the differences and similarities in approaches, resources, and learning methodologies employed by both types of schools. Utilizing a qualitative approach, data was collected through interviews with deputy headmasters and heads of enterprises from selected public and private schools. The findings reveal significant differences in curricula, teaching methods, assessment practices, and teacher quality between the two types of schools. Public schools tend to emphasize student interactivity with a student-centered approach, while private schools are characterized by the use of modern technology and resources in learning. Despite these differences, both public and private schools share similarities in their commitment to improving the quality of teaching. Both types of schools invest in enhancing teacher competence through continuous training and professional development. The study concludes that although there are differences and similarities in approaches, resources, and learning methodologies in public and private schools, the quality of teachers and their commitment to improving teaching quality have a positive impact on both. This research provides valuable insights into the factors influencing learning quality in public and private schools, highlighting the crucial role of teachers and quality management in creating an effective and relevant learning environment for students.